Impact of transcutaneous electrical acupoint stimulation on postoperative recovery in older adults following pterygium excision: a prospective randomized controlled trial - Wu, Xinlu; Huang, Ledan; Sun, Huanhuan; Chen, Yating; Guo, Haibo; Wang, Yuchen; Pan, Jingye; Wang, Xinxin; Mo, Yunchang; Dai, Qinxue (Frontiers in Neurology, 2025)
ObjectiveThe aim of this study is to evaluate the effect of transcutaneous electrical acupoint stimulation (TEAS) during the perioperative period on the quality of postoperative recovery among patients undergoing pterygium excision.MethodsA total of 110 patients scheduled for unilateral pterygium excision were enrolled and randomly assigned in equal numbers to the TEAS group or the control group. In the TEAS group, patients received TEAS at the LI4 and PC6 acupoints, initiated 30 min before anesthesia induction and continued until the conclusion of surgery. In the control group, patients had electrode pads applied without active stimulation. Numerical Rating Scale (NRS) scores, State–Trait Anxiety Inventory (S-TAI) scores, and Quality of Recovery-40 Questionnaire (QoR-40) scores were collected from both groups.ResultsNo statistically significant differences were observed in baseline demographic and clinical characteristics between the two groups. At 24 h postoperatively, patients in the TEAS group demonstrated significantly higher QoR-40 scores and significantly lower NRS pain scores and postoperative SAI scores compared to the control group.ConclusionTEAS was effective in reducing postoperative pain and anxiety levels while enhancing the quality of postoperative recovery in patients undergoing pterygium surgery.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR2200056062.